Correlates of hypertension in patients with AIDS in the era of highly-active antiretroviral therapy - Krauskopf, Katherine (2013)
BACKGROUND: It is unclear whether HIV-related factors modify risk for hypertension (HTN). In a cohort of patients with AIDS, we determined HTN incidence and prevalence and assessed associated traditional, HIV-specific, and retinal vasculature factors. METHODS: Prospective observational cohort, 2,390 patients with AIDS (1998–2011). Univariate analysis was used to assess the impact of traditional and AIDS-related risk factors on HTN prevalence and incidence. Multivariate regression analyses were used to evaluate the adjusted impact of these factors. RESULTS: HTN prevalence was 22% (95% CI 21–24%) and was associated with traditional HTN risk factors (age, Black race, higher weight) as well as diabetes, hyperlipidemia, time since AIDS diagnosis and higher CD4+ T cell counts. HTN incidence was 64.1/1000 person-years (95% CI 58.7/1000 – 69.9/1000). Age, race, weight and diabetes were associated with incident HTN, but HIV-specific factors were not. CONCLUSIONS: HTN, a prevalent cardiovascular risk factor in patients with AIDS, is associated with traditional and metabolic risk factors.